2001
DOI: 10.1007/s001250051578
|View full text |Cite
|
Sign up to set email alerts
|

Male-to-female excess in diabetes diagnosed in early adulthood is not specific for the immune-mediated form nor is it HLA-DQ restricted: possible relation to increased body mass index

Abstract: The pathologic process underlying Type I diabetes is believed to be driven by the interplay of environmental triggers that are largely not known and multiple genetic factors that have been partly identified [1±6]. HLA genes play a major part in genetic susceptibility and protection, the highest risk being conferred by the heterozygous combination of the two most prominent risk haplotypes DR4-DQA1*0301-DQB1*0302 and DR3-DQA1*0501-DQB1*0201 [1,2,5]. The role of the variable number of tandem repeats Diabetologia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 27 publications
9
39
0
Order By: Relevance
“…In all nine centres the estimated male to female ratio of Type 1 diabetes incidence was greater than one in the 15 to 29 age group and greater than in children. In the age group 25 to 29 years the male to female incidence rate ratio was equal to or greater than 1.5 in all centres, although this was not statistically significant in Antwerp and Leicestershire, the two centres with the smallest study populations [21,31]. However, the Belgian Diabetes Registry has shown a significant difference between incidence rates in men and women (p<0.001) in the age range 15 to 39 years [21,32].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In all nine centres the estimated male to female ratio of Type 1 diabetes incidence was greater than one in the 15 to 29 age group and greater than in children. In the age group 25 to 29 years the male to female incidence rate ratio was equal to or greater than 1.5 in all centres, although this was not statistically significant in Antwerp and Leicestershire, the two centres with the smallest study populations [21,31]. However, the Belgian Diabetes Registry has shown a significant difference between incidence rates in men and women (p<0.001) in the age range 15 to 39 years [21,32].…”
Section: Discussionmentioning
confidence: 76%
“…A Belgian study failed to confirm the finding of HLA restriction with regard to the male to female excess in young adulthood, but did not completely rule out the suggestion of an interaction between an X-linked genetic factor and high-risk HLA types as a route to diabetes [31].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Vitamin D-deficient NOD mice are lighter and smaller at 15 days of age but they reach the same weight as control mice around weaning at 30 days of age. This lower weight during the first days of life, probably due to the vitamin D deficiency of the dams, followed by a more rapid weight gain in the weeks thereafter might be another factor contributing to the diabetes presentation since also in humans, rapid growth and weight gain are implicated in Type 1 diabetes acceleration through increased metabolic demand [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Belgian study however, found that this male bias is age-dependent, is not present in diagnosed patients younger than 15 years of age, and is independent of the presence of anti-islet autoantibodies or HLA type, suggesting that insulin resistance can play a role. [7].…”
Section: Introductionmentioning
confidence: 99%